Evaluating the Use of a Thermal Sensor to Detect Small Ground-Nesting Birds in Semi-Arid Environments during Winter - J. Silverio Avila-Sanchez; Humberto L. Perotto-Baldivieso; Lori D. Massey; J. Alfonso Ortega-S.; Leonard A. Brennan; Fidel Hernández (Drones, 2024)
Aerial wildlife surveys with fixed-wing airplanes and helicopters are used more often than on-the-ground field surveys to cover areas that are both extensive and often inaccessible. Drones with high-resolution thermal sensors are being widely accepted as research tools to aid in monitoring wildlife species and their habitats. Therefore, our goal was to assess the feasibility of detecting northern bobwhite quail (Colinus virginianus, hereafter ‘bobwhite’) using drones with a high-resolution thermal sensor. Our objectives were (1) to identify the altitudes at which bobwhites can be detected and (2) compare the two most used color palettes to detect species (black-hot and isotherm). We achieved this goal by performing drone flights at different altitudes over caged tame bobwhites and capturing still images and video recordings at altitudes from 18 to 42 m. We did not observe or detect any obvious signs of distress, movement, or fluttering of bobwhites inside cages caused by the noise or presence of the drone during data acquisition. We observed the highest counts of individual bobwhites with the black-hot thermal palette at 18 m (92%; <semantics><mover accent="true">x¯</mover></semantics> = 47 bobwhites; SE = 0.41) and at 24 m (81%; <semantics><mover accent="true">x¯</mover></semantics> = 41 bobwhites; SE = 0.89). The isotherm thermal palette had lower count proportions. The use of video to count quail was not feasible due to the low resolution of the video and the species size. Flying drones with high-resolution thermal sensors provided reliable imagery to detect roosting bobwhite individuals in South Texas during the winter.